UV photocureable coating, preparation method thereof and application of UV photocureable coating in automobiles

By using modified epoxy resin, epoxy acrylate resin and other materials in automotive coatings, UV light curing coatings with self-healing and flame retardant properties are prepared, which solves the problems of scratching and flammability of existing coatings, and improves the performance and safety of the coating.

CN119614045AActive Publication Date: 2025-03-14BAOHONG COATINGS (GUANGDONG) CO LTD

Patent Information

Application Number
CN202411950937.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-14
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Existing automotive paints are prone to scratches during use, and the coating composition is flammable, lacking self-repair and flame retardant properties.

Method used

UV photocuring coatings are prepared through specific reaction and mixing methods by using modified epoxy resin, epoxy acrylate resin, modified graphene, functional boron oxide hexacycline and 1,6-hexanediol diacrylate, which give them self-healing and flame retardant properties.

Benefits of technology

Improves the mechanical properties, self-repairing properties and flame retardant properties of UV light curing coatings, and enhances the scratch resistance and safety of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005214857490000031
    Figure BDA0005214857490000031
Patent Text Reader

Abstract

The invention discloses a UV photocureable coating as well as a preparation method and application thereof in automobiles, and relates to the technical field of coatings. When the UV photocureable coating is prepared, 4-aminophenylboronic acid is dehydrated to prepare aminated boron oxygen six-ring; carrying out a reaction on the aminated boroxane and diallyl chlorophosphate to prepare functionalized boroxane; the preparation method comprises the following steps: sequentially reacting graphene oxide with 3-chloropropyltriethoxysilane and 1, 3-diallyl-1, 3, 5-triazine-2, 4, 6-triketone, so as to obtain modified graphene; the preparation method comprises the following steps: reacting epoxy resin with 2-butenal thiosemicarbazone to prepare modified epoxy resin; and uniformly mixing the modified epoxy resin, the epoxy acrylate resin, the modified graphene, the functionalized boroxane, the 1, 6-hexanediol diacrylate and the 1-hydroxycyclohexyl phenyl ketone, so as to obtain the UV photocureable coating. The UV photocureable coating prepared by the invention has excellent flame retardant, self-repairing and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to a UV light-curing coating and a preparation method thereof and application in automobiles. Background Art

[0002] With the development of the national economy, the sales volume of automobiles has been rising year by year. The rapid growth of automobile sales volume has effectively driven the sustainable development of automobile coatings and painting business, and brought huge business opportunities to the automobile coatings industry. Automobile coatings not only give automobiles a colorful appearance, meeting people's increasingly diverse individual needs, but also effectively prevent the surface of automobiles from corrosion, wear and chemical erosion by forming a protective film, thereby extending the service life of the automobile. UV light-curing coatings have the characteristics of fast curing speed, no volatile organic compounds generated during the curing process, environmental friendliness and low energy consumption, and have received more and more attention in the field of automobile coatings.

[0003] During the use of the car, the coating on the surface of the car body is easily scratched by various objects, which not only affects the appearance, but also weakens the protective effect of the coating on the car body; in addition, most of the components in the coating are organic compounds and polymers, which are highly flammable. Therefore, it is very necessary to invent a UV light-curing coating with self-repairing and flame-retardant properties. Summary of the invention

[0004] The purpose of the present invention is to provide a UV light-curing coating and a preparation method thereof and application in automobiles, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A UV light-curing coating, comprising, by weight: 26 to 30 parts of modified epoxy resin, 18 to 22 parts of epoxy acrylate resin, 3 to 4 parts of modified graphene, 6 to 8 parts of functionalized boroxane, 40 to 42 parts of 1,6-hexanediol diacrylate, and 1 to 2 parts of 1-hydroxycyclohexyl phenyl ketone;

[0007] The modified epoxy resin is prepared by reacting epoxy resin and 2-butenal thiosemicarbazone;

[0008] The modified graphene is prepared by reacting pre-modified graphene and 1,3-diallyl-1,3,5-triazine-2,4,6-trione;

[0009] The pre-modified graphene is prepared by reacting graphene oxide and 3-chloropropyltriethoxysilane;

[0010] The functionalized boroxane is prepared by reacting boroxane amination and diallyl chlorophosphate;

[0011] The aminated boroxene is prepared by dehydrating 4-aminophenylboronic acid.

[0012] A method for preparing a UV light-curing coating, the method comprising the following steps:

[0013] (1) mixing boroxane and acetonitrile in a mass ratio of 1:(8-10) to prepare a boroxane solution; mixing diallyl chlorophosphate, triethylamine and acetonitrile in a mass ratio of 1:(0.03-0.05):(10-12) which is 3 times the molar amount of boroxane, and adding the boroxane solution dropwise at a constant speed within 10 minutes at 50-60°C and 300-500 r / min stirring conditions, continuing to stir and react for 4-5 hours, and drying at 58-60°C under vacuum conditions for 7-9 hours to obtain a functionalized boroxane;

[0014] (2) Pre-modified graphene, 1,3-diallyl-1,3,5-triazine-2,4,6-trione, triethylamine, and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:(3-4):(0.01-0.02):(30-40), stirred at 400-600 r / min and 90-100° C. for 9-11 h, filtered, washed with anhydrous ethanol and deionized water for 3-5 times each, and dried at 65-75° C. for 10-12 h under vacuum conditions to obtain modified graphene;

[0015] (3) Weigh 26-30 parts of modified epoxy resin, 18-22 parts of epoxy acrylate resin, 3-4 parts of modified graphene, 6-8 parts of functionalized borax, 40-42 parts of 1,6-hexanediol diacrylate, and 1-2 parts of 1-hydroxycyclohexyl phenyl ketone, by mass; mix the modified epoxy resin, epoxy acrylate resin, modified graphene, functionalized borax, 1,6-hexanediol diacrylate, and 1-hydroxycyclohexyl phenyl ketone uniformly to prepare a UV light-curing coating.

[0016] As an optimization, the preparation method of the aminoboryl hexacyclopentane in step (1) is: 4-aminophenylboronic acid and chloroform are mixed uniformly in a mass ratio of 1:(8-10), placed in a high-pressure reactor, and stirred at 75-85°C and 300-500r / min for 20-24h under nitrogen protection, and dried at 58-60°C for 6-7h under vacuum conditions to obtain the aminoboryl hexacyclopentane.

[0017] As an optimization, the reaction process of the functionalized hexacyclic borane in step (1) is as follows:

[0018]

[0019] As an optimization, the preparation method of the pre-modified graphene in step (2) is: graphene oxide and anhydrous ethanol are mixed uniformly in a mass ratio of 1: (70-80), 20-24 times the mass of graphene oxide chloropropylsilane hydrolyzate is added, the mixture is stirred at 55-65° C. and 400-500 r / min for 3-4 hours, filtered, washed with anhydrous ethanol for 3-5 times, and dried at 70-80° C. under vacuum conditions for 9-11 hours to obtain pre-modified graphene.

[0020] As an optimization, the preparation method of the chloropropylsilane hydrolyzate is: 3-chloropropyltriethoxysilane and anhydrous ethanol are mixed uniformly in a mass ratio of 1:(45-55), the pH is adjusted to 4.5-5.5 with an oxalic acid aqueous solution with a molar concentration of 1-1.5 mol / L, and the mixture is stirred at 10-30° C. and 400-500 r / min for 20-30 min to prepare a chloropropylsilane hydrolyzate.

[0021] As an optimization, the manufacturer of the graphene oxide is Zhongke Leiming (Beijing) Technology Co., Ltd.

[0022] As an optimization, the preparation method of the modified epoxy resin in step (3) is: epoxy resin, 2-butenal thiosemicarbazone and toluene are mixed uniformly in a mass ratio of 1: (0.3-0.4): (8-10), stirred at 50-60° C. and 600-800 r / min for 2-3 h under nitrogen protection, and dried at 50-60° C. for 10-12 h under vacuum conditions to obtain the modified epoxy resin.

[0023] As an optimization, the model of the epoxy resin is E51, and the manufacturer is Jinan Xinzhenyuan Chemical Co., Ltd.

[0024] As an optimization, the model of the epoxy acrylate resin in step (3) is HWC-6104Y, and the manufacturer is Suzhou Huiwangcheng Chemical Co., Ltd.

[0025] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0026] When preparing UV light-curing coating, the present invention comprises the following steps: dehydrating 4-aminophenylboronic acid to obtain aminoboroxane; reacting aminoboroxane and diallyl chlorophosphate to obtain functionalized boroxane; reacting graphene oxide and 3-chloropropyltriethoxysilane to obtain pre-modified graphene; reacting pre-modified graphene and 1,3-diallyl-1,3,5-triazine-2,4,6-trione to obtain modified graphene; reacting epoxy resin and 2-butenal thiosemicarbazone to obtain modified epoxy resin; and uniformly mixing modified epoxy resin, epoxy acrylate resin, modified graphene, functionalized boroxane, 1,6-hexanediol diacrylate and 1-hydroxycyclohexyl phenyl ketone to obtain UV light-curing coating.

[0027] Firstly, the boric acid on 4-aminophenylboronic acid is dehydrated by heat to form a boroxy hexacyclic ring, thereby obtaining an amino boroxy hexacyclic ring; the amino group on the amino boroxy hexacyclic ring is reacted with the chlorine atom on diallyl chlorophosphate to obtain a functionalized boroxy hexacyclic ring, and a carbon-carbon double bond and a phosphorus element are introduced into the functionalized boroxy hexacyclic ring; the carbon-carbon double bond introduced into the functionalized boroxy hexacyclic ring can participate in the curing process of the UV light-curing coating, increase the cross-linking site, form a cross-linking network, inhibit the relative slip between the molecular chains, and improve the mechanical properties of the UV light-curing coating after curing; the introduction of the phosphorus element can improve the flame retardant properties of the UV light-curing coating; the boroxy hexacyclic ring is a reversible dynamic covalent bond, which can achieve dynamic cross-linking under heating or the action of Lewis base or water molecules; during the use of the car, the surface coating is easily scratched and scratched, which affects the appearance of the car and the protection of the metal materials inside the car body. Considering the use environment of the car, the boroxy hexacyclic ring is introduced into the UV light-curing coating to give the UV light-curing coating a self-healing property.

[0028] Secondly, graphene oxide and 3-chloropropyltriethoxysilane are reacted to obtain pre-modified graphene, and chlorine atoms are introduced into the pre-modified graphene oxide; the chlorine atoms on the pre-modified graphene are reacted with the secondary amine on 1,3-diallyl-1,3,5-triazine-2,4,6-trione to obtain modified graphene; carbon-carbon double bonds and cyanuric acid structures are introduced into the modified graphene, and the carbon-carbon double bonds introduced into the modified graphene can participate in the curing process of the UV light-curing coating, increase the cross-linking sites, form a cross-linking network, inhibit the relative slip between molecular chains, and improve the mechanical properties of the UV light-curing coating after curing; the cyanuric acid structure will produce non-flammable gas when heated, dilute the oxygen concentration, and improve the flame retardant properties of the UV light-curing coating; the addition of graphene oxide can increase the strength and hardness of the coating, improve the wear resistance of the coating, modify the graphene oxide, increase the dispersibility of the graphene oxide in the coating, and give full play to the reinforcing effect of the graphene oxide.

[0029] Finally, the epoxy group on the epoxy resin is reacted with the amino group on the 2-butenal thiosemicarbazone to obtain a modified epoxy resin; a carbon-carbon double bond and a thiosemicarbazone structure are introduced into the modified epoxy resin. The carbon-carbon double bond introduced into the modified epoxy resin can participate in the curing process of the UV light-curing coating, and the thiosemicarbazone structure has a coordination effect and can form a complex with metal ions such as Fe, Cu, Zn, Pd, Pt, and Ni; during the use of the car, the surface coating is easily scratched and scratched, which affects the appearance of the car and the protection of the metal materials inside the car body. The introduction of the thiosemicarbazone structure allows the coating to chelate with the metal ions escaped from the metal materials inside the car body to form a cross-linked network structure, further improving the self-healing performance of the UV light-curing coating. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] The manufacturer of the graphene oxide used in the following examples and comparative examples is Zhongke Leiming (Beijing) Technology Co., Ltd.; the epoxy resin model used is E51, and the manufacturer is Jinan Xinzhenyuan Chemical Co., Ltd.

[0032] Embodiment 1:

[0033] A method for preparing a UV light-curing coating, the method comprising the following steps:

[0034] (1) 4-aminophenylboronic acid and chloroform were mixed in a mass ratio of 1:8, placed in a high-pressure reactor, stirred at 75°C and 300 r / min for 24 hours under nitrogen protection, and dried at 58°C for 7 hours to obtain borylamine; borylamine and acetonitrile were mixed in a mass ratio of 1:8 to prepare borylamine solution; diallyl chlorophosphate, triethylamine and acetonitrile (3 times the molar amount of borylamine) were mixed in a mass ratio of 1:0.03:10, and the borylamine solution was added dropwise at a uniform rate within 10 minutes under 50°C and 300 r / min stirring conditions, and the stirring reaction was continued for 5 hours. Under vacuum conditions, it was dried at 58°C for 9 hours to obtain functionalized borylamine;

[0035] (2) 3-Chloropropyltriethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:45, the pH was adjusted to 4.5 with an aqueous solution of oxalic acid with a molar concentration of 1 mol / L, and the mixture was stirred at 10°C and 400 r / min for 30 min to prepare a chloropropylsilane hydrolyzate; graphene oxide and anhydrous ethanol were mixed at a mass ratio of 1:70, 20 times the mass of graphene oxide was added to the chloropropylsilane hydrolyzate, and the mixture was stirred at 55°C and 400 r / min for 4 h, filtered, and filtered. The pre-modified graphene was washed with water and ethanol for 3 times, and dried at 70°C for 11 hours under vacuum conditions to obtain pre-modified graphene; the pre-modified graphene, 1,3-diallyl-1,3,5-triazine-2,4,6-trione, triethylamine, and N,N-dimethylformamide were mixed uniformly at a mass ratio of 1:3:0.01:30, stirred at 400 r / min and 90°C for 11 hours, filtered, washed with anhydrous ethanol and deionized water for 3 times each, and dried at 65°C for 12 hours under vacuum conditions to obtain modified graphene;

[0036] (3) Epoxy resin, 2-butenal thiosemicarbazone and toluene were mixed uniformly in a mass ratio of 1:0.3:8, and stirred at 50°C and 600 r / min for 3 h under nitrogen protection, and dried at 50°C for 12 h under vacuum conditions to obtain a modified epoxy resin; 26 parts of modified epoxy resin, 18 parts of epoxy acrylate resin, 3 parts of modified graphene, 6 parts of functionalized boroxane, 40 parts of 1,6-hexanediol diacrylate and 1 part of 1-hydroxycyclohexyl phenyl ketone were weighed by mass; the modified epoxy resin, epoxy acrylate resin, modified graphene, functionalized boroxane, 1,6-hexanediol diacrylate and 1-hydroxycyclohexyl phenyl ketone were mixed uniformly to obtain a UV light-curing coating.

[0037] Embodiment 2:

[0038] A method for preparing a UV light-curing coating, the method comprising the following steps:

[0039] (1) 4-aminophenylboronic acid and chloroform were mixed in a mass ratio of 1:9, placed in a high-pressure reactor, stirred at 80°C and 400 r / min for 22 hours under nitrogen protection, and dried at 59°C for 6.5 hours under vacuum conditions to obtain boroxane; boroxane and acetonitrile were mixed in a mass ratio of 1:9 to prepare boroxane solution; diallyl chlorophosphate, triethylamine, and acetonitrile, which were 3 times the molar amount of boroxane, were mixed in a mass ratio of 1:0.04:11, and the boroxane solution was added dropwise at a uniform rate within 10 minutes under stirring conditions of 55°C and 400 r / min, and the stirring reaction was continued for 4.5 hours. Under vacuum conditions, it was dried at 59°C for 8 hours to obtain functionalized boroxane;

[0040] (2) 3-Chloropropyltriethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:50, the pH was adjusted to 5 with an aqueous solution of oxalic acid with a molar concentration of 1.25 mol / L, and stirred at 20°C and 450 r / min for 25 min to prepare a chloropropylsilane hydrolyzate; graphene oxide and anhydrous ethanol were mixed at a mass ratio of 1:75, 22 times the mass of graphene oxide was added to the chloropropylsilane hydrolyzate, and the mixture was stirred at 60°C and 450 r / min for 3.5 h, filtered, and filtered. The pre-modified graphene was washed with water and ethanol for 4 times, and dried at 75°C for 10 hours under vacuum conditions to obtain pre-modified graphene; the pre-modified graphene, 1,3-diallyl-1,3,5-triazine-2,4,6-trione, triethylamine, and N,N-dimethylformamide were mixed uniformly at a mass ratio of 1:3.5:0.015:35, stirred at 500r / min and 95°C for 10 hours, filtered, washed with anhydrous ethanol and deionized water for 4 times each, and dried at 70°C for 11 hours under vacuum conditions to obtain modified graphene;

[0041] (3) Epoxy resin, 2-butenal thiosemicarbazone and toluene were mixed uniformly in a mass ratio of 1:0.35:9, and stirred at 55°C and 700 r / min for 2.5 h under nitrogen protection, and dried at 55°C for 11 h under vacuum conditions to obtain a modified epoxy resin; 28 parts of modified epoxy resin, 20 parts of epoxy acrylate resin, 3.5 parts of modified graphene, 7 parts of functionalized boroxane, 41 parts of 1,6-hexanediol diacrylate and 1.5 parts of 1-hydroxycyclohexyl phenyl ketone were weighed by mass; the modified epoxy resin, epoxy acrylate resin, modified graphene, functionalized boroxane, 1,6-hexanediol diacrylate and 1-hydroxycyclohexyl phenyl ketone were mixed uniformly to obtain a UV light-curing coating.

[0042] Embodiment 3:

[0043] A method for preparing a UV light-curing coating, the method comprising the following steps:

[0044] (1) 4-aminophenylboronic acid and chloroform were mixed in a mass ratio of 1:10, placed in a high-pressure reactor, stirred at 85°C and 500 r / min for 20 hours under nitrogen protection, and dried at 60°C for 6 hours to obtain borylamine; borylamine and acetonitrile were mixed in a mass ratio of 1:10 to prepare borylamine solution; diallyl chlorophosphate, triethylamine and acetonitrile (3 times the molar amount of borylamine) were mixed in a mass ratio of 1:0.05:12, and the borylamine solution was added dropwise at a uniform rate within 10 minutes at 60°C and 500 r / min. The reaction was continued with stirring for 4 hours, and dried at 60°C for 7 hours under vacuum to obtain functionalized borylamine;

[0045] (2) 3-Chloropropyltriethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:55, the pH was adjusted to 5.5 with an aqueous solution of oxalic acid with a molar concentration of 1.5 mol / L, and the mixture was stirred at 30°C and 500 r / min for 20 min to prepare a chloropropylsilane hydrolyzate; graphene oxide and anhydrous ethanol were mixed at a mass ratio of 1:80, 24 times the mass of graphene oxide was added to the chloropropylsilane hydrolyzate, and the mixture was stirred at 65°C and 500 r / min for 3 h, filtered, and used The pre-modified graphene was washed with anhydrous ethanol for 5 times, and dried at 80°C for 9 hours under vacuum conditions to obtain pre-modified graphene; the pre-modified graphene, 1,3-diallyl-1,3,5-triazine-2,4,6-trione, triethylamine, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:4:0.02:40, stirred at 600r / min and 100°C for 9 hours, filtered, washed with anhydrous ethanol and deionized water for 5 times each, and dried at 75°C for 10 hours under vacuum conditions to obtain modified graphene;

[0046] (3) Epoxy resin, 2-butenal thiosemicarbazone and toluene were mixed uniformly in a mass ratio of 1:0.4:10, stirred at 60°C and 800 r / min for 2 h under nitrogen protection, and dried at 60°C for 10 h under vacuum conditions to obtain a modified epoxy resin; 30 parts of modified epoxy resin, 22 parts of epoxy acrylate resin, 4 parts of modified graphene, 8 parts of functionalized boroxane, 42 parts of 1,6-hexanediol diacrylate and 2 parts of 1-hydroxycyclohexyl phenyl ketone were weighed by mass; the modified epoxy resin, epoxy acrylate resin, modified graphene, functionalized boroxane, 1,6-hexanediol diacrylate and 1-hydroxycyclohexyl phenyl ketone were mixed uniformly to obtain a UV light-curing coating.

[0047] Comparative Example 1:

[0048] The preparation method of the UV light-curing coating of Comparative Example 1 is different from that of Example 2 in step (1), and step (1) is modified as follows: 4-vinylbenzeneboronic acid and chloroform are mixed uniformly in a mass ratio of 1:9, placed in a high-pressure reactor, stirred at 80° C. and 400 r / min for 22 h under nitrogen protection, and dried at 59° C. for 6.5 h under vacuum conditions to obtain a functionalized hexaborane. The remaining steps are the same as those of Example 2.

[0049] Comparative Example 2:

[0050] The preparation method of the UV light-curing coating of Comparative Example 2 is different from that of Example 2 in that step (1) is not performed, and step (3) is modified as follows: epoxy resin, 2-butenal thiosemicarbazone, and toluene are uniformly mixed in a mass ratio of 1:0.35:9, stirred and reacted at 55°C and 700r / min for 2.5h under nitrogen protection, and dried at 55°C for 11h under vacuum conditions to obtain a modified epoxy resin; 28 parts of modified epoxy resin, 20 parts of epoxy acrylate resin, 3.5 parts of modified graphene, 41 parts of 1,6-hexanediol diacrylate, and 1.5 parts of 1-hydroxycyclohexyl phenyl ketone are weighed by mass; the modified epoxy resin, epoxy acrylate resin, modified graphene, 1,6-hexanediol diacrylate, and 1-hydroxycyclohexyl phenyl ketone are uniformly mixed to obtain a UV light-curing coating. The remaining steps are the same as those of Example 2.

[0051] Comparative Example 3:

[0052] The preparation method of the UV light-curing coating of Comparative Example 3 is different from that of Example 2 in that step (2) is not performed, and step (3) is modified as follows: epoxy resin, 2-butenal thiosemicarbazone, and toluene are uniformly mixed in a mass ratio of 1:0.35:9, stirred and reacted at 55°C and 700r / min for 2.5h under nitrogen protection, and dried at 55°C for 11h under vacuum conditions to obtain a modified epoxy resin; 28 parts of modified epoxy resin, 20 parts of epoxy acrylate resin, 3.5 parts of graphene oxide, 7 parts of functionalized boroxane, 41 parts of 1,6-hexanediol diacrylate, and 1.5 parts of 1-hydroxycyclohexyl phenyl ketone are weighed by mass; the modified epoxy resin, epoxy acrylate resin, graphene oxide, functionalized boroxane, 1,6-hexanediol diacrylate, and 1-hydroxycyclohexyl phenyl ketone are uniformly mixed to obtain a UV light-curing coating. The remaining steps are the same as those of Example 2.

[0053] Comparative Example 4:

[0054] The preparation method of the UV light-curing coating of Comparative Example 4 is different from that of Example 2 only in step (3), and step (3) is modified as follows: epoxy resin, 3-aminopropylene, and toluene are mixed uniformly in a mass ratio of 1:0.35:9, stirred and reacted at 55°C and 700r / min for 2.5h under nitrogen protection, and dried at 55°C for 11h under vacuum conditions to obtain a modified epoxy resin; 28 parts of modified epoxy resin, 20 parts of epoxy acrylate resin, 3.5 parts of modified graphene, 7 parts of functionalized boroxane, 41 parts of 1,6-hexanediol diacrylate, and 1.5 parts of 1-hydroxycyclohexyl phenyl ketone are weighed by mass; the modified epoxy resin, epoxy acrylate resin, modified graphene, functionalized boroxane, 1,6-hexanediol diacrylate, and 1-hydroxycyclohexyl phenyl ketone are mixed uniformly to obtain a UV light-curing coating. The remaining steps are the same as those of Example 2.

[0055] Test Example 1

[0056] Mechanical properties testing

[0057] Test method: Pour the examples and comparative examples into a polytetrafluoroethylene mold and heat them at an energy density of 800 mW / cm 2 The cured samples were irradiated with ultraviolet light for 15 seconds at a radiation distance of 20 cm. The cured samples of the embodiment and the comparative example were cut into standard strips according to GB / T13022, and the tensile strength of the standard strips was tested on an electronic universal testing machine. The results are shown in Table 1.

[0058] Table 1

[0059] Tensile strength(MPa) Tensile strength(MPa) Example 1 74.83 Comparative Example 1 73.35 Example 2 75.21 Comparative Example 2 60.14 Example 3 73.96 Comparative Example 3 63.27 Comparative Example 4 73.44

[0060] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the UV light-curing coating prepared by the present invention has good mechanical properties.

[0061] By comparison, the tensile strength of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that the amino group on the aminoboryl oxide hexacycle reacts with the chlorine atom on diallyl chlorophosphate to obtain a functionalized boryl oxide hexacycle, and a carbon-carbon double bond is introduced into the functionalized boryl oxide hexacycle; the carbon-carbon double bond introduced into the functionalized boryl oxide hexacycle can participate in the curing process of the UV light-curing coating, increase the cross-linking sites, form a cross-linking network, inhibit the relative slip between molecular chains, and improve the mechanical properties of the UV light-curing coating after curing.

[0062] By comparison, the tensile strength of Examples 1 to 3 is greater than that of Comparative Example 3, indicating that pre-modified graphene is obtained by reacting graphene oxide and 3-chloropropyltriethoxysilane, and chlorine atoms are introduced into the pre-modified graphene oxide; the chlorine atoms on the pre-modified graphene react with the secondary amine on 1,3-diallyl-1,3,5-triazine-2,4,6-trione to obtain modified graphene; and carbon-carbon double bonds are introduced into the modified graphene. The carbon-carbon double bonds introduced into the modified graphene can participate in the curing process of the UV light-curing coating, increase cross-linking sites, form a cross-linking network, inhibit the relative slip between molecular chains, and improve the mechanical properties of the UV light-curing coating after curing.

[0063] Test Example 2

[0064] Self-healing performance test

[0065] Test method: Prepare the standard sample in the same way as in Test Example 1, and test the tensile strength B1 of the standard sample on an electronic universal testing machine. Cut a 2mm deep and 20mm long crack in the middle of the standard sample, immerse it in a 6% copper ion aqueous solution, let it stand for 30 minutes, take it out, keep it at 70°C for 12 hours, cool it to room temperature to obtain the repaired standard sample, test the tensile strength B2 of the repaired standard sample, and calculate the self-repair rate of the standard sample, self-repair rate = tensile strength B2 / tensile strength B1×100%. The results are shown in Table 2.

[0066] Table 2

[0067] Self-repair rate (%) Self-repair rate (%) Example 1 97.36 Comparative Example 1 97.04 Example 2 98.25 Comparative Example 2 80.83 Example 3 97.63 Comparative Example 3 96.93 Comparative Example 4 86.41

[0068] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be found that the UV light-curing coating prepared by the present invention has good self-repairing performance.

[0069] By comparison, the self-repairing rates of Examples 1 to 3 are greater than that of Comparative Example 2, indicating that the boric acid on 4-aminophenylboronic acid is dehydrated by heat to form a boroxy hexacyclic ring, thereby obtaining an amino boroxy hexacyclic ring; the boroxy hexacyclic ring is a reversible dynamic covalent bond, which achieves dynamic crosslinking under the action of heating or Lewis base or water molecules, thereby giving the UV light-curing coating self-repairing properties.

[0070] By comparison, the self-repairing rates of Examples 1 to 3 are greater than that of Comparative Example 4, indicating that the epoxy group on the epoxy resin is reacted with the amino group on the 2-butenal thiosemicarbazone to obtain a modified epoxy resin; a thiosemicarbazone structure is introduced into the modified epoxy resin, and the thiosemicarbazone structure has a coordination effect and can form a complex with metal ions such as Fe, Cu, Zn, Pd, Pt, and Ni; the introduction of the thiosemicarbazone structure allows the coating to chelate with the metal ions escaped from the metal material inside the car body to form a cross-linked network structure, thereby further improving the self-repairing performance of the UV light-curing coating.

[0071] Test Example 3

[0072] Flame retardant performance test

[0073] Test method: Pour the examples and comparative examples into a polytetrafluoroethylene mold and heat them at an energy density of 800 mW / cm 2 The cured samples were irradiated with ultraviolet light for 15 seconds at a radiation distance of 20 cm. The cured samples of the embodiment and the comparative example were cut into standard specimens according to GB / T2406.2, and the limiting oxygen index of the standard specimens was tested. The results are shown in Table 3.

[0074] Table 3

[0075] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 28.85 Comparative Example 1 24.62 Example 2 29.34 Comparative Example 2 23.33 Example 3 29.07 Comparative Example 3 24.06 Comparative Example 4 28.61

[0076] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the UV light-curing coating prepared by the present invention has good flame retardant properties.

[0077] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Examples 1 to 2, indicating that the amino group on the aminoboryl oxide hexacycle reacts with the chlorine atom on diallyl chlorophosphate to obtain a functionalized boryl oxide hexacycle, and phosphorus is introduced into the functionalized boryl oxide hexacycle; the introduction of phosphorus can improve the flame retardant properties of UV light-curing coatings.

[0078] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 3, indicating that graphene oxide and 3-chloropropyltriethoxysilane are reacted to obtain pre-modified graphene, and chlorine atoms are introduced into the pre-modified graphene oxide; the chlorine atoms on the pre-modified graphene are reacted with the secondary amine on 1,3-diallyl-1,3,5-triazine-2,4,6-trione to obtain modified graphene; and a cyanuric acid structure is introduced into the modified graphene, and the cyanuric acid structure introduced into the modified graphene generates non-flammable gas when heated, dilutes the oxygen concentration, and improves the flame retardant properties of the UV light-curing coating.

[0079] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A UV light curing coating, characterized in that: Calculated by mass, it includes: 26 to 30 parts of modified epoxy resin, 18 to 22 parts of epoxy acrylate resin, 3 to 4 parts of modified graphene, 6 to 8 parts of functionalized borane, 40 to 42 parts of 1,6-hexanediol diacrylate, and 1 to 2 parts of 1-hydroxycyclohexyl phenyl ketone; The modified epoxy resin is prepared by reacting epoxy resin and 2-butenal thiosemicarbazone; The modified graphene is prepared by reacting pre-modified graphene and 1,3-diallyl-1,3,5-triazine-2,4,6-trione; The pre-modified graphene is prepared by reacting graphene oxide and 3-chloropropyltriethoxysilane; The functionalized boroxane is prepared by reacting boroxane amination and diallyl chlorophosphate; The aminated boroxene is prepared by dehydrating 4-aminophenylboronic acid.

2. A method for preparing a UV light-curing coating, characterized in that: The preparation method of the UV light-curing coating comprises the following preparation steps: (1) mixing boroxane and acetonitrile in a mass ratio of 1:(8-10) to prepare a boroxane solution; mixing diallyl chlorophosphate, triethylamine and acetonitrile in a mass ratio of 1:(0.03-0.05):(10-12) which is 3 times the molar amount of boroxane, and adding the boroxane solution dropwise at a constant speed within 10 minutes at 50-60°C and 300-500 r / min stirring conditions, continuing to stir and react for 4-5 hours, and drying at 58-60°C under vacuum conditions for 7-9 hours to obtain a functionalized boroxane; (2) Pre-modified graphene, 1,3-diallyl-1,3,5-triazine-2,4,6-trione, triethylamine, and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:(3-4):(0.01-0.02):(30-40), stirred at 400-600 r / min and 90-100° C. for 9-11 h, filtered, washed with anhydrous ethanol and deionized water for 3-5 times each, and dried at 65-75° C. for 10-12 h under vacuum conditions to obtain modified graphene; (3) Weigh 26-30 parts of modified epoxy resin, 18-22 parts of epoxy acrylate resin, 3-4 parts of modified graphene, 6-8 parts of functionalized borax, 40-42 parts of 1,6-hexanediol diacrylate, and 1-2 parts of 1-hydroxycyclohexyl phenyl ketone, by mass; mix the modified epoxy resin, epoxy acrylate resin, modified graphene, functionalized borax, 1,6-hexanediol diacrylate, and 1-hydroxycyclohexyl phenyl ketone uniformly to prepare a UV light-curing coating.

3. The method for preparing a UV light-curing coating according to claim 2, characterized in that: The preparation method of the aminoboryl hexacyclopentane in step (1) is as follows: 4-aminophenylboronic acid and chloroform are mixed uniformly in a mass ratio of 1:(8-10), placed in a high-pressure reactor, stirred at 75-85°C and 300-500r / min for 20-24h under nitrogen protection, and dried at 58-60°C for 6-7h under vacuum conditions to obtain the aminoboryl hexacyclopentane.

4. The method for preparing a UV light-curing coating according to claim 2, characterized in that: The preparation method of the pre-modified graphene in step (2) is as follows: graphene oxide and anhydrous ethanol are uniformly mixed in a mass ratio of 1: (70-80), 20-24 times the mass of graphene oxide chloropropylsilane hydrolyzate is added, the mixture is stirred at 55-65° C. and 400-500 r / min for 3-4 hours, filtered, washed with anhydrous ethanol for 3-5 times, and dried at 70-80° C. under vacuum conditions for 9-11 hours to obtain the pre-modified graphene.

5. The method for preparing a UV light-curing coating according to claim 4, characterized in that: The preparation method of the chloropropylsilane hydrolyzate is as follows: 3-chloropropyltriethoxysilane and anhydrous ethanol are uniformly mixed in a mass ratio of 1:(45-55), the pH value is adjusted to 4.5-5.5 with an oxalic acid aqueous solution with a molar concentration of 1-1.5 mol / L, and the mixture is stirred at 10-30° C. and 400-500 r / min for 20-30 min to prepare the chloropropylsilane hydrolyzate.

6. The method for preparing a UV light-curing coating according to claim 2, characterized in that: The preparation method of the modified epoxy resin in step (3) is as follows: epoxy resin, 2-butenal thiosemicarbazone and toluene are uniformly mixed in a mass ratio of 1:(0.3-0.4):(8-10), stirred at 50-60°C and 600-800r / min for 2-3h under nitrogen protection, and dried at 50-60°C for 10-12h under vacuum conditions to obtain the modified epoxy resin.

7. The method for preparing a UV light-curing coating according to claim 6, characterized in that: The model of the epoxy resin is E51.

8. The method for preparing a UV light-curing coating according to claim 2, characterized in that: The model of the epoxy acrylate resin in step (3) is HWC-6104Y.

9. Use of a UV light-curing coating prepared by the method for preparing a UV light-curing coating according to any one of claims 2 to 8 in automobiles.

Citation Information

Patent Citations

  • Epoxy resin adhesive and preparation method and application thereof

    CN110713814A

  • Self-repairing polyurethane based on boroxine and preparation method of self-repairing polyurethane

    CN113563559A

  • Preparation method of novel flame retardant modified epoxy resin adhesive film

    CN115851199A

  • Meltable intumescent flame retardant compositions

    US20190359824A1

Cited By

  • High-thermal-conductivity Mini LED packaging film and preparation method thereof

    CN121064606A

  • High-thermal-conductivity mini LED packaging film and preparation method thereof

    CN121064606B

  • Polyethylene composite packaging material and preparation method thereof

    CN122060238A

  • Polyethylene composite packaging material and method for producing the same

    CN122060238B